Synergism between vastus lateralis and vastus medialis oblique during gait after anterior cruciate ligament reconstruction - Leporace, Gustavo; Zeitoune, Gabriel Gollner; Vivacqua, Thiago; Metsavaht, Leonardo; Oliveira, Liszt Palmeira de; Batista, Luiz Alberto (Acta Fisiátrica, 2019)
Objective: The aim of this study was to compare vastus lateralis and vastus medialis oblique (VL/VMO) muscle co-contraction (MCC) and activation ratio during gait between healthy subjects- control group (CG), and those with anterior cruciate ligament reconstruction (ACLR). Methods: Twenty-three subjects participated in this study, 14 CG and 9 ACLR. The myoelectric activities of the VL and VMO were captured to calculate the MCC. The VL/VMO ratio was obtained by dividing the normalized signals of these two muscles at each point of the curve. The MCC values and the activation ratio in the initial double limb stance, single limb stance, terminal double limb stance and swing were obtained by calculating the arithmetic mean of the intensity values ​​of the common curve in each interval. Results: MCC was significantly lower in the ACLR group during the initial double limb stance phase (p=0.001), with a high effect size (1.72). No significant differences were found for the other comparisons. Conclusions: The results of this study showed that the VL and VMO muscles co-contraction in the initial double limb stance phase of gait was different between the healthy and ACLR individuals. This finding may be related to lower patellofemoral stability during the loading response, increasing the potential risk for the development of injuries in this joint.